Chemical Assessment Of Seasonal Variations For 2021-2022 And 2022-2023 In Water Quality Of Annamayya Project On Cheyyeru River (Journal of Namibian Studies : History Politics Culture, 2023)
Water spread diseases are increased day by day due to lack of awareness of water pollution and its contamination in rivers. In the current research an investigation has been carried out to examine quality of water in Cheyyeru River. The main objective of present research work is to compute the Water Quality Index and to investigate its suitability for drinking purpose in Cheyyeru River water, Annamayya dam. Water samples were taken during both seasons of pre- and post-monsoon. The different laboratory chemical water parameter tests such as Electric conductivity ,Total Suspended Solids ,pH, Nitrogen, Biological Oxygen Demand, Chlorine, Total Dissolved Solids, chemical oxygen demand , dissolved Oxygen , phosphorous, sulfur and potassium are conducted and analyzed for drinking purposes. From the laboratory investigation it is observe that all parameters of water quality are within the WHO permissible limits. Therefore, study is useful for agriculture and agro-ecological planning.